Wann beginnt die Papierzeit?: zur Wissensgeschichte eines hoch- und spätmittelalterlichen Beschreibstoffs - Meyer-Schlenkrich, Carla (Materiale Textkulturen, 2024)
Parchment or paper? The choice between these two writing materials was available to people in Italy from 1100, to those north of the Alps from the thirteenth century. If we take them by their word, they preferred the traditional animal skin. But in the hands of writers, paper took over on a broad front. This study analyzes the quiet revolution quantitatively and qualitatively, and investigates why it was so silent